Antibiotic prescribing in Danish general practice in the elderly population from 2010 to 2017. (2nd October 2021) - Veimer Jensen, Maria Louise; Aabenhus, Rune Munck; Holzknecht, Barbara Juliane; Bjerrum, Lars; Jensen, Jette Nygaard; Siersma, Volkert; Córdoba, Gloria
Abstract: Objective: This study aimed to describe prescription of antibiotics to the elderly population in general practice in Denmark from 2010–2017. Design: This is a national register-based observational study. Setting: General practice, Denmark Main outcome measure: The main outcome measure was prescriptions/1, 000 inhabitants/day (PrID) in relation to year, age and sex, indication, and antibiotic agent. Subjects: In this study, we included inhabitants of Denmark, ≥65 years of age between 01st July 2010–30th June 2017. Results: A total of 5, 168, 878 prescriptions were included in the study. Antibiotic prescriptions decreased from 2.2 PrID to 1.7 (-26.9%, CI95% [-31.1;-22.4]) PrID during the study. The decrease in PrID was most noticeable among 65–74-year-olds (-25%). The ≥85-year-olds were exposed to twice as many PrID than the 65–74-year-olds, but only accounted for 20% of the total use. Urinary tract infection (UTI) was the most common indication for antibiotic prescription and increased with advancing age. The most commonly prescribed antibiotics were pivmecillinam and phenoxymethylpenicillin. Prescribing with no informative indication was present in one third of all cases. Conclusion: The prescription of antibiotics in the elderly population in general practice decreased from 2010 to 2017. The oldest age group was exposed twice as frequently to antibiotic prescriptions as the 65–74-year-olds. The smallest reduction was observed for the ≥85-year-olds, suggesting targeting interventions at this group. Key Points: High antibiotic use among elderly is well known and studies indicate mis- and overuse within this population. Our study shows. The prescription rate is decreasing within all age groups of the elderly population. The ≥85-year-olds receive twice as many prescriptions/1000/day as the 65–74-years-olds.